Розподіл майна подружжя як спосіб вирішення сімейного спору - Nykyforak, Volodymyr; Никифорак, Володимир Михайлович (Чернівецький національний університет. Видавництво "Рута"., 2009)
Purpose of this article there was a decision of essence of mechanism of section of joint property of the married couples. In obedience to a law the direct section of property of the married couples can be produced both during marriage and after his dissolution. However much judicial practice testifies that the voluntarily order of section of property of the married couples has a positive result rarely. In this connection, all basic methods of judicial section of joint property of the married couples are considered in the article, and also the alternative methods of decision of domestic dispute are certain about the section of joint property.
Keywords: спільна власність; спільна сумісна власність подружжя; поділ майна; розподіл майна подружжя